Penggunaan Agregat dari Sungai Sarambu Ratte Balla Kecamatan Bittuang Kabupaten Tana Toraja Sebagai Campuran Beton - Luciana Buarlele; Erni Rante Bungin; Alias Belopa (Paulus Civil Engineering Journal, 2025)
The Sarambu Ratte Balla River has a fairly clean aggregate, which can be seen visually with a clear river flow, making the Sarambu Ratte Balla river one of the sources of aggregate that can be utilised by the local community. The purpose of this study was to assess the compressive strength, split tensile strength, and flexural strength.This research was conducted at the Structure and Materials Laboratory, Siipiil Engineering Study Programme, Faculty of Engineering, University of Indonesia Paulus University. Method used in the mix design is SNI 7656:2012. The actual compressive strength test results for the design mix of 25 MPa concrete at 28 days reached 25.832 MPa, with a splitting tensile strength of 2.475 MPa and a flexural strength of 2.441 MPa, all meeting the design strength criteria for concrete. The actual compressive strength test results for the design mix of 30 MPa concrete at 28 days reached 30.451 MPa, with a splitting tensile strength of 2.875 MPa and a flexural strength of 3.146 MPa. Conclusion in this study has good results as a concrete mixture. This can be observed from the results of concrete testing that meets the quality of the plan, namely 25 MPa and 30 MPa.